2021
DOI: 10.1038/s41598-021-83075-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of the COVID-19 pandemic: controlled sanitary deconfinement in Portugal

Abstract: The COVID-19 pandemic has forced policy makers to decree urgent confinements to stop a rapid and massive contagion. However, after that stage, societies are being forced to find an equilibrium between the need to reduce contagion rates and the need to reopen their economies. The experience hitherto lived has provided data on the evolution of the pandemic, in particular the population dynamics as a result of the public health measures enacted. This allows the formulation of forecasting mathematical models to an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 41 publications
0
53
0
1
Order By: Relevance
“…We include the asymptomatic carriers of the SARS-CoV-2, who are nevertheless able to spread the virus. The reason to include them is that asymptomatic people are very important contributors in the spread of the SARS-CoV-2, and this subpopulation has been considered in other studies related to the COVID-19 pandemic [20,72,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. It has been found that quantitative SARS-CoV-2 viral loads were similarly high for infected individuals with symptoms, pre-symptomatic, or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…We include the asymptomatic carriers of the SARS-CoV-2, who are nevertheless able to spread the virus. The reason to include them is that asymptomatic people are very important contributors in the spread of the SARS-CoV-2, and this subpopulation has been considered in other studies related to the COVID-19 pandemic [20,72,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. It has been found that quantitative SARS-CoV-2 viral loads were similarly high for infected individuals with symptoms, pre-symptomatic, or asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the pandemic of COVID-19, a number of attempts to predict its evolution have been published, helping the health authorities with their strategies. The mathematical tools used vary from compartmental models [1][2][3][4][5], including fractional derivatives [6,7], to statistical tools [8][9][10]. With the aim of helping health authorities to avoid hospital resource collapses, some works have been used, e.g., to predict the numbers of required beds at intensive care units [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of 2020, numerous studies have been published on COVID-19 and SARS-CoV-2 in fields ranging from microscopic to macroscopic, including molecular biology, medical and clinical studies, epidemiology, and political decision making, with each field applying its characteristic methodologies. As examples of reports with similar focus and methodology to this study, research on COVID-19 modelling has considered countries or regions such as France [22], Italy [23], the Basque country [24], Spain [25], Portugal [26], Hong Kong [27], China [28,29,30], and the UK [31]. These studies discussed recurrence and rebound of the epidemics, effects of protection measures and lockdown, widespread testing, contact tracing, care capacities, or scenarios of pandemic management.…”
Section: Introductionmentioning
confidence: 99%